The Effects Of Printing Parameters On The Tensile Properties Of 3D Printed Thermoplastic Polyurethane (TPU) Via Fused Deposition Modeling (FDM) Method - Poul Dawas, Emiellia (Universiti Sains Malaysia, 2022)
In this research work, the primary purpose is to obtain an optimized printing parameters for the 3D printed thermoplastic polyurethane (TPU) using the fused deposition modeling (FDM) process to have non-defective parts and achieve higher tensile strength that is suitable for biomedical applications. The 3D printing parameters studied in this research were the printing speed (35 mm/s, 50 mm/s) and infill density (30%, 65%, 100%). The raw materials used for the FDM method are TPU filaments with two different shore hardness (72D and 98A). Different shore hardness of TPU was used to investigate how different hardness will affect the tensile strength. The thermal properties, rheological behaviour and its chemical composition were analyzed via differential scanning calorimetry (DSC), melt flow index (MFI), and Fourier transform infrared spectroscopy (FTIR) for the filaments. DSC analysis was set in the temperature range of 25 - 280 ℃ and it was used to study the melting temperature and crystallization of TPU 72D and 98A. The glass transition temperature (Tg) and exothermic peaks for both TPU filaments were not present as TPUs Tg temperature is shifted to much lower temperature and no cooling steps are being conducted. MFI test was used to evaluate the flow rate of the thermoplastic filaments and the results showed that 98A has higher MFI than 72D. A higher MFI contributes to lower viscosity, whereas lower MFI corresponds to a larger molecular weight. The physical and mechanical properties were evaluated via optical microscope (OM), scanning electron microscopy (SEM), tensile test, and density test of the 3D printed dumbbell shape of 72D and 98A. The density test data showed that in overall, 72D 2samples exhibit the highest density compared to 98A since 72D has more hard segments (HS) count present in its structure compared to 98A. Tensile test data showed that TPU 98A exhibited higher tensile strength and elongation at break compared to 72D but lower in terms of the tensile modulus. Hence, the non-defective part and higher tensile strength of 3D printed TPU 98A had achieved the desired mechanical properties, as the result parameters at 35 mm/s of printing speed and 65% of infill density showed the best parameters for a 3D printer.